Primerjava učnih načrtov in vključenost priporočil za medpredmetno povezovanje likovnih vsebin - Birsa, Eda (Revija za elementarno izobraževanje, 2017)
Comparison of Syllabi and Inclusion of Recommendations for Interdisciplinary Integration of Visual Arts Contents. We applied qualitative analysis to the syllabi of all subjects from the 1st up to the 5th grade of basic school in Slovenia in order to find out in what ways they contain recommendations for interdisciplinary integration. We classified them into three categories: references to subjects, implicit references, and explicit references. The classification into these categories has shown that certain concepts foreseen for integration with visual arts education in individual subjects for a certain grade or for a particular educational cycle cannot be found in the visual arts syllabus.
Keywords: visual arts; syllabus for visual arts education; integrated teaching process of visual arts education; elementary school; interdisciplinary integration